Synergistic effect of Cobalt and Iron in Layered Double Hydroxide Catalysts for the Oxygen Evolution Reaction - Yang, Fengkai; Sliozberg, Kirill; Masa, Justus (ChemSusChem, 2017)
Co-based layered double hydroxide (LDH) catalysts with Fe and Al contents in the range of 15 to 45 at % were synthesized by an efficient coprecipitation method. In these catalysts, Fe3+ or Al3+ ions play an essential role as trivalent species to stabilize the LDH structure. The obtained catalysts were characterized by a comprehensive combination of surface- and bulk-sensitive techniques and were evaluated for the oxygen evolution reaction (OER) on rotating disk electrodes. The OER activity decreased upon increasing the Al content for the Co- and Al-based LDH catalysts, whereas a synergistic effect in Co- and Fe-based LDHs was observed, which resulted in an optimal Fe content of 35 at %. This catalyst was spray-coated on Ni foam electrodes and showed very good stability in a flow-through cell with a potential of approximately 1.53 V at 10 mA cm−2 in 1 m KOH for at least 48 h.